2013
DOI: 10.1371/journal.pone.0060829
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Virus Resistance in Transgenic Maize Expressing a dsRNA-Specific Endoribonuclease Gene from E. coli

Abstract: Maize rough dwarf disease (MRDD), caused by several Fijiviruses in the family Reoviridae, is a global disease that is responsible for substantial yield losses in maize. Although some maize germplasm have low levels of polygenic resistance to MRDD, highly resistant cultivated varieties are not available for agronomic field production in China. In this work, we have generated transgenic maize lines that constitutively express rnc70, a mutant E. coli dsRNA-specific endoribonuclease gene. Transgenic lines were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In addition, maize expressing an E. coli ribonuclease specific for double-stranded RNA had increased resistance to RBSDV (Cao et al 2013).…”
Section: Other Potential Virus Resistance Genesmentioning
confidence: 99%
“…In addition, maize expressing an E. coli ribonuclease specific for double-stranded RNA had increased resistance to RBSDV (Cao et al 2013).…”
Section: Other Potential Virus Resistance Genesmentioning
confidence: 99%
“…Natural infection, evaluated in disease nurseries or "hot spots" where the disease was naturally endemic or prevalent, was among the early approaches used (Findley et al, 1976). This method continues to be effective for identifying virus-resistant germplasm and characterizing resistance genes and QTLs in maize (Cao et al, 2013;Di Renzo et al, 2004, Ming et al, 1997. However, this approach does not ensure gain under selection, because of unequal disease pressure from season to season and the high risk of escapes.…”
Section: Screening Methodsmentioning
confidence: 99%
“…Interestingly, transgenic plants expressing SCMV (MDMV-B) were resistant to that virus, but also had pleiotropic resistance to MCMV (Murry et al, 1993). Further, transgenic maize expressing a bacterial dsRNAspecific nuclease (RNAse III) was resistant to RBSDV (Cao et al, 2013), but it is not yet known if this line is resistant to multiple viruses. The MSV-expressing transgenic maize are still being tested in confined field trials (Tomson & Shepherd, 2010), and lines expressing the MDMV P1 provided some virus resistance in the field .…”
Section: Pathogen Resistance In Maizementioning
confidence: 99%
“…Since, ACMV is a DNA virus and its gene expression takes place on viral mini-chromosome structure, viral resistant transgenic cassava was also obtained using hairpin RNA construct targeting the viral promoter for transcriptional gene silencing (hp-TGS) (Vanderschuren et al, 2007). Though, the effectiveness of the transgenic viral resistance has been tested in field trial for many generations (Shimizu et al, 2011; Cao et al, 2013; Wang et al, 2016), currently no SRGE based staple food crop was reported for commercial release.…”
Section: Application Status Of Srge In Crop Protectionmentioning
confidence: 99%